Modified surface of duplex stainless steel using tig torch and diffusion techniques - Maleque, Md. Abdul; Paijan, Lailatul Harina (2017)
Surface modified duplex stainless steel (DSS) is very attractive material for a wide range of high temperature uses including tribological application. Melting technique using tungsten inert gas (TIG) torch and diffusion technique using gas nitriding are the effective processing routes with simple and cost effective way. In this invention, TIG torch melting technique is used to develop composite coating on DSS with the preplacement of SiC ceramic particles. Finding showed that the hard layer produce the dense and thick coating with good metallurgical bonding to the base material.In nitriding process, thermal heat acts as a catalyst for the decomposition of ammonia into nascent nitrogen which diffuse into DSS surface. Hard surface layer produce the dense coating with better wear resistance.Both techniques shared improved hardness and better wear resistance. However, TIG torch melting technique is more promising compared to nitriding technique.